2021
DOI: 10.1186/s12885-021-08333-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of self-help workbook intervention on quality of life in cancer patients receiving chemotherapy: results of a randomized controlled trial

Abstract: Background A self-help workbook is expected to support cancer patients to cope with physical and psychosocial distress, to facilitate communication with medical staff, and to improve quality of life (QOL). We conducted a randomized controlled trial to evaluate the effectiveness of a self-help workbook intervention on QOL and survival. Methods From June 2014 to March 2015, patients with breast, colorectal, gastric, and lung cancer receiving outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Despite its burden and relatively high prevalence among breast cancer patients (ranging from 60 to 90%) [ 9 ], CRF remains underestimated and mistreated, and little is known about the underlying risk factors. Understanding the contributing factors would allow the implementation of adequate targeted interventions for better management and quality of care [ 2 , 7 , 10 ]. Several hypotheses have been suggested to identify the predisposing factors to higher sensitivity for tiredness, including neurobiological dysfunctions (alterations in the hypothalamic-pituitary-adrenal (HPA) axis [ 11 ] and the autonomic nervous system responsiveness [ 12 , 13 ]), pro-inflammatory cytokines and cellular immune system dysregulations [ 14 , 15 ], psychological disorders such as depression, anxiety, and sleep disorders [ 16 , 17 ], cancer treatments (e.g., regimen type, chemotherapy agents, doses) [ 18 ], in addition to other factors related to physical adaptability, pain [ 19 , 20 ], or genetic predisposition [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its burden and relatively high prevalence among breast cancer patients (ranging from 60 to 90%) [ 9 ], CRF remains underestimated and mistreated, and little is known about the underlying risk factors. Understanding the contributing factors would allow the implementation of adequate targeted interventions for better management and quality of care [ 2 , 7 , 10 ]. Several hypotheses have been suggested to identify the predisposing factors to higher sensitivity for tiredness, including neurobiological dysfunctions (alterations in the hypothalamic-pituitary-adrenal (HPA) axis [ 11 ] and the autonomic nervous system responsiveness [ 12 , 13 ]), pro-inflammatory cytokines and cellular immune system dysregulations [ 14 , 15 ], psychological disorders such as depression, anxiety, and sleep disorders [ 16 , 17 ], cancer treatments (e.g., regimen type, chemotherapy agents, doses) [ 18 ], in addition to other factors related to physical adaptability, pain [ 19 , 20 ], or genetic predisposition [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, CBT-AP was found to be a feasible and potentially efficacious intervention for breast cancer patients undergoing chemotherapy. Another study conducted on cancer patients had shown that self-help workbook intervention was feasible in cancer patients receiving chemotherapy, although the effect of the intervention was limited ( 42 ). The discrepancy between the effects of intervention might be because the intervention was guided by a trained therapist in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To support cancer patients in coping with physical and psychological distress, Takano et al [ 9 ] developed a self-help workbook. The workbook is intended to improve communication with medical staff and improve quality of life.…”
Section: Introductionmentioning
confidence: 99%